2004
DOI: 10.1007/s00268-004-6825-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Several Agents for Preventing Postoperative Adhesions

Abstract: Postoperative adhesions (PAs) are usually clinically asymptomatic. Symptomatic cases, however, may present with chronic abdominal and pelvic pain, infertility, and intestinal obstruction; and they may require intensive, costly therapeutic modalities. Various agents have been used to prevent PAs, but the results indicate general suboptimal effectiveness. Our objective was to evaluate the comparative effectiveness of two pharmacologic agents for preventing PA: nadroparine calcium (low-molecular-weight heparin, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
(18 reference statements)
0
23
0
2
Order By: Relevance
“…However, when the fibrin also contains cellular elements, it may undergo organization into adhesion. Some researchers have studied antiadhesive agents, which stimulate fibrinolysis or prevent organization of the fibrin matrix [23,24]. However, barriers between the two surfaces are thought to be the most effective method for preventing postoperative adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the fibrin also contains cellular elements, it may undergo organization into adhesion. Some researchers have studied antiadhesive agents, which stimulate fibrinolysis or prevent organization of the fibrin matrix [23,24]. However, barriers between the two surfaces are thought to be the most effective method for preventing postoperative adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in the control group received no barrier. On the 14th day after surgery, all rats in each group underwent repeat laparotomy under anesthesia and the extent of adhesion formation was evaluated according to our modified scale [21]. Adhesion severity was scored as follows: 0 = no adhesion; 1 = thin and easily separated adhesion; 2 = narrow range weak adhesion, but able to withstand mild traction; 3 = adhesion present in two locations or fairly firm adhesion, and 4 = adhesion present in three or more locations (fig.…”
Section: Methodsmentioning
confidence: 99%
“…Standard heparin and LMWH's inhibit thrombin formation that is effective in the coagulation phase of the phases of wound healing. It has been reported that heparin and derivatives fasten wound healing by decreasing the destruction in tissues and cells, and increasing neoangiogenesis, thus, supporting revascularization, granulation, and epithelisation (12,13). In addition, heparin and derivatives positively affect wound healing by increasing the cellular aggregation and new vessel formation, and by decreasing cellular destruction (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In the light of these results, the weak spot of many studies on peritoneal lavage is use of 0.9% saline as a control fluid for other tested substances (7,15,16). Many investigators and clinicians simply denote this solution as a standard fluid for lavage of inflamed peritoneal cavities (17), and there is still no convincing evidence concerning the biocompatibility of this peritoneal lavage solution.…”
Section: Discussionmentioning
confidence: 99%